Geographic, bathymetric and inter-annual variability in the distribution of Liocarcinus depurator (Brachyura: Portunidae) along the Mediterranean coast of the Iberian peninsula - Marta M. Rufino; Pere Abello; Andrew B. Yule; Pedro Torres (Scientia Marina, 2005)
The patterns of occurrence and density of Liocarcinus depurator along the western Mediterranean coast (from Gibraltar to Cape Creus) were measured at depths between 25 and 800 m. Bottom trawl surveys were carried out from 1994 to 2003. For analysis, the area was divided into eight geographic sectors and eight depth intervals. The highest crab occurrences (~80% of trawls) and densities (985 crabs km-2 on average) were found on the shallow muddy continental shelf at depths of 51-100 m with the next highest densities on the upper slope between 201 and 300 m depth (~130 crabs km-2 on average) and occurrence (66% of trawls) between 301 and 400 m. Below 500 m, both crab occurrence and density dropped sharply and L. depurator occurred in less than 10% of all trawls. Thus L. depurator appears to slightly avoid areas on the continental shelf break which are characterised by coarser sediments than on the adjacent continental shelf and slope. Geographically, maximum crab occurrence and density were observed off Valencia (86%, 1187 crabs km-2) and West Alborán (83%, 974 crabs km-2), followed by the Ebro Delta (75%, 502 crabs km-2). Off Alicante L. depurator were relatively common (74% of trawls) but at lower densities (294 crabs km-2 on average). Abundance off the coast of North Catalonia (317 crabs km-2) was equivalent to that off Alicante but the crabs were generally less common (53% of trawls). In general, the highest densities of L. depurator occurred in areas with a wide continental shelf and muddy sediments. During the ten years from 1994 to 2003, densities decreased at a rate of 8 and 4% per annum in shallower water and water deeper than 150 m respectively with a similar decrease in percentage occurrence. This pattern is discussed in relation to the physiological tolerance of the species and reported trends of warming in the Mediterranean Sea.